2018
DOI: 10.1002/advs.201800748
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared‐Plasmonic Energy Upconversion in a Nonmetallic Heterostructure for Efficient H2 Evolution from Ammonia Borane

Abstract: Plasmonic metal nanostructures have been widely used to enhance the upconversion efficiency of the near‐infrared (NIR) photons into the visible region via the localized surface plasmon resonance (LSPR) effect. However, the direct utilization of low‐cost nonmetallic semiconductors to both concentrate and transfer the NIR‐plasmonic energy in the upconversion system remains a significant challenge. Here, a fascinating process of NIR‐plasmonic energy upconversion in Yb3+/Er3+‐doped NaYF4 nanoparticles (NaYF4:Yb‐Er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 45 publications
0
43
0
Order By: Relevance
“…[45] Besides, the localized surface plasmon resonance (LSPR) field can also be used to enhance the emission intensity of the upconversion materials. Dong and co-workers have prepared NaYF 4 : Yb, Er/W 18 O 49 nanowire heterostructures [46] as shown in Figure 4i. Due to the abundant vacancies, W 18 O 49 nanowire have enough free electrons to present LSPR effect [26,[47][48] as confirmed by the SPR absorption peak in the Figure 4j.…”
Section: Upconversion Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[45] Besides, the localized surface plasmon resonance (LSPR) field can also be used to enhance the emission intensity of the upconversion materials. Dong and co-workers have prepared NaYF 4 : Yb, Er/W 18 O 49 nanowire heterostructures [46] as shown in Figure 4i. Due to the abundant vacancies, W 18 O 49 nanowire have enough free electrons to present LSPR effect [26,[47][48] as confirmed by the SPR absorption peak in the Figure 4j.…”
Section: Upconversion Materialsmentioning
confidence: 99%
“…[45] i) SEM image of NaYF 4 : Yb, Er/W 18 O 49 nanowire heterostructures. [46] j) Transmittance spectra of W18O49 nanowires (1), N-W18O49 nanowires (2), wavelength. [46] Eventhough the lanthanide-based upconversion materials can help to activate the photocatalytic systems under the NIR irradiation, there are natural bottlenecks for these photocatalytic systems.…”
Section: Upconversion Materialsmentioning
confidence: 99%
“…Complexing tungsten-based photocatalysts with other materials to form novel heterojunctions is also an efficient pathway to adjust the charge carrier concentration and improve the fullspectrum photocatalytic activities. NaYF 4 : Yb 3+ -Er 3+ sensitized W 18 O 49 nanowires exhibit distinct improved catalytic H 2 evolution from ammonia borane (BH 3 NH 3 ) upon irradiation at the wavelength of 980 nm [69]. As shown in Fig.…”
Section: Other Kinds Of Tungsten-based Heterojunctionsmentioning
confidence: 92%
“…While, in strictly, hydrogen generation from ammonia decomposition do not give direct evidence to show the energy transfer from solar light to chemicals. Then, Zhang et al reported photocatalytic hydrogen generation by plasmonic hot electrons of heterostructural W 18 O 49 /g‐C 3 N 4 under visible–NIR light irradiation . Therefore, nonmetallic plasmonic NPs are promising SPR materials for photocatalysis.…”
Section: Introductionmentioning
confidence: 99%